High Systolic Blood Pressure, Anterior Segment Changes and Visual Impairment Independently Predict Sickle Cell Retinopathy - Idris, Ibrahim M; Yusuf, Aminu A.; Gwarzo, Dalha H. (My University, 2021)
Sickle cell disease is often complicated by retinopathy, which can be proliferative or non proliferative. Proliferative sickle cell retinopathy potentially leads to blindness. There is a paucity of data on sickle cell disease-related retinopathy from Africa, where the disease is most prevalent. We aimed to determine the clinical, ophthalmic, and laboratory predictors of sickle cell retinopathy in an African population. We conducted a cross-sectional study of 262 participants, aged 13 years and above, with sickle cell disease. Demographic and clinical data were collected using a structured questionnaire and standard physical examinations. Vitreo-retinal specialists performed eye examinations on all the participants. Hematological and biochemical assessments were conducted using standard methods. A multivariate stepwise forward logistic regression was performed to determine the predictors of retinopathy. The median age of the participants was 20 years (interquartile range: 17–25 years). Most of the participants had a homozygous Hb S (HBB: c.20A>T) genotype (96.9%), with 3.1% who carried a Hb S/Hb C (HBB: c.19G>A) genotype. The prevalence of non proliferative sickle cell retinopathy was 24.4%. Only 1.9% had proliferative sickle cell retinopathy (PSCR). Elevated systolic blood pressure (BP) [odds ratio (OR): 6.85, 95% confidence interval (95% CI): 1.05–44.45, p ¼ 0.059], moderate visual impairment (OR: 5.2, 95% CI: 1.39–19.63, p ¼ 0.015), and anterior segment changes (OR: 2.21, 95% CI: 1.19–4.13, p ¼ 0.012) were independently predictive of retinopathy. This study provides new insight into predictors of retinopathy in sickle cell disease, with implications on early screening and prevention
Keywords: Ophthalmic changes; predictors; sickle cell disease; ACE: Genetic Medicine; WAGMC; University of Ghana; Musbahu S. Kurawa; Abdulsalam Shuaib; Aisha A. Galadanci